Mycobacterium tuberculosis Proteasome Accessory Factor A (PafA) Can Transfer Prokaryotic Ubiquitin-Like Protein (Pup) between Substrates - Susan Zhang (American Society for Microbiology, 2017)
ABSTRACT The protein degradation machinery of Mycobacterium tuberculosis includes a proteasome and a ubiquitin-like protein (Pup). Proteasome accessory factor A (PafA) attaches Pup to proteins to target them for degradation by the proteasome. Free Pup is unstable and never observed in extracts of M. tuberculosis, an observation that led us to hypothesize that PafA may need alternative sources of Pup. Here, we show that PafA can move Pup from one proteasome substrate, inositol 1-phosphate synthetase (Ino1), to two different proteins, malonyl coenzyme A (CoA)-acyl carrier protein transacylase (FabD) and lonely guy (Log). This apparent “transpupylation” reaction required a previously unrecognized depupylase activity in PafA, and, surprisingly, this depupylase activity was much more efficient than the activity of the dedicated depupylase Dop (deamidase of Pup). Thus, PafA can potentially use both newly synthesized Pup and recycled Pup to doom proteins for degradation. IMPORTANCE Unlike eukaryotes, which contain hundreds of ubiquitin ligases, Pup-containing bacteria appear to have a single ligase to pupylate dozens if not hundreds of different proteins. The observation that PafA can depupylate and transpupylate in vitro offers new insight into how protein stability is regulated in proteasome-bearing bacteria. Importantly, PafA and the dedicated depupylase Dop are each required for the full virulence of Mycobacterium tuberculosis. Thus, inhibition of both enzymes may be extremely attractive for the development of therapeutics against tuberculosis.